The sentence model as the main unit defining sentence structure (Eurasian Journal of Philology Science and Education, 2016)
Problems of typology of the sentence structure and the concept «sentence model» as the main characteristic unit is considered in the article. For defining the model of the sentence it is suggested to take structural semantic components of the sentence which reflect categorial-semantic meanings of the syntaxeme in the sentence structure as the basis. In other words, the semantic-grammatical characteristics of the components of the sentence are regarded as the basis for defining the concept «sentence model» and its main features are revealed.Sentence model is the main unit of classification of types of sentences in the language. In the structure of the model, not general grammatical predicative meaning, but distinctions in the form and meaning of the main components of the sentence are essential.The main sentence models in modern the Kazakh language are defined on this base.
Keywords: sentence model; sentence structure; structural semantic sentences; type of sentence; sentence typology; classification of types of sentence; component sentence structure.